IOT-based temperature and humidity monitoring over data logger thingspeak using Arduino uno / Nur Hafieez Nasri - Nasri, Nur Hafieez (2024)
Temperature and humidity are useful variables and often measured for various applications in a variety of locations, including football field, farms, greenhouses, hospitals, industrial buildings, homes, and workplaces for monitoring purpose as for well- being as well as safety precautions. For instance, excessive temperature and humidity could influence our thermal comfort, and cause impact on human health. With this motivation, a data logger for monitoring temperature and humidity is developed in this study using Arduino UNO which offer remote access and control through IoT. In addition, ThingSpeak platform is utilized for visualization of the measured data while the controlling is done by the Blynk module. The project involves both simulation and hardware prototype development. The results showed that the simulation model of the data logger is successfully developed and outputs the expected outcomes. On the other hand, the data logger model operates successfully and is capable of logging temperature and humidity data over time.